Legal Analysis of the Impact of Elements of Bribery and Giving Gratification in the Perspective of Anti- Corruption Law in Indonesia - Gilang Gemilang; Sumarno Sumarno; Suci Ramadhani (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
The rampant corruption that continues to be demonstrated by public officials makes it seem as if the law has run out of ways to overcome it. And corruption is a type of crime that is only committed by people who have high intellectual capacity and ability. They continue to try how to avoid corruption crimes, so one of the methods they use is the pattern of giving gifts which is actually intended as a form of bribery. This study analyzes the concept of bribery and gratification and the parameters that differentiate between the two as regulated in several Articles of the Corruption Eradication Law. This involves the application of normative legal research supported by court decisions to clarify the differences. The results of this study indicate that bribery requires a meeting of minds between the bribe giver and the bribe recipient which is not found in the decision . The reporting mechanism and reversal of the burden of proof do not apply to bribery while the sting operation does not apply to gratification because it cannot meet the provisions of Article 1 number 19 of the Criminal Procedure Code. Criminal sanctions are also imposed on both the giver and the recipient of the bribe, while the act of the giver of gratification is not a criminal act. Keywords: reversal of burden of proof, caught red-handed, reporting mechanism .